1982
DOI: 10.1002/ajp.1350030131
|View full text |Cite
|
Sign up to set email alerts
|

A vocabulary of abnormal behaviors in restrictively reared chimpanzees

Abstract: The purpose of this paper is to establish a vocabulary for the systematic documentation of abnormal behavior in restrictively reared chimpanzees. Such a vocabulary facilitates communication regarding the range of behavior patterns indicative of psychopathology. The behavior of restrictively reared chimpanzees was observed and descriptive statistics on abnormal behaviors are presented. Succinct descriptive terminology is developed to aid in documentation of the range of abnormal behavior observed in restrictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 6 publications
3
56
0
Order By: Relevance
“…However, this conclusion is based on data from a limited number of subjects (n = 4 and n = 6, respectively) and should be replicated with additional subjects. Other studies have shown that primates in socially restrictive environments use inanimate enrichment more than primates housed in larger social groups [Walsh et al, 1982;Maki et al, 1989;Bloomsmith et al, 1990b;Schapiro et al, 1992]. It is possible that the socially housed subjects in this study, who were isolated during the testing periods, were preoccupied with the activities of their group members in the adjacent outdoor enclosure.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, this conclusion is based on data from a limited number of subjects (n = 4 and n = 6, respectively) and should be replicated with additional subjects. Other studies have shown that primates in socially restrictive environments use inanimate enrichment more than primates housed in larger social groups [Walsh et al, 1982;Maki et al, 1989;Bloomsmith et al, 1990b;Schapiro et al, 1992]. It is possible that the socially housed subjects in this study, who were isolated during the testing periods, were preoccupied with the activities of their group members in the adjacent outdoor enclosure.…”
Section: Discussionmentioning
confidence: 80%
“…In some circumstances, individual housing can cause primates to develop social deficiencies [Harlow, 1960;Harlow and Harlow, 1962;Mason, 1968;Davenport and Rogers, 1970;Davenport, 1979;Fritz, 1986] and other stereotypical behaviors [Davenport et al, 1970;Maple, 1979;Markowitz, 1982;Walsh et al, 1982]. These behaviors are often difficult to extinguish, even after the animals are socially grouped or are introduced to more stimulating environments [Pfeiffer and Koebner, 1978;Walsh et al, 1982;Clarke et al, 1982;Fritz, 1986]. To help avoid the development of such behavioral problems, increased attention has been devoted to developing enrichment programs for individually housed primates [Brent et al, 1989a;Fajzi et al, 1989;Schapiro and Bloomsmith, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…Barahal, 1940;Buxbaum, I960], Unlike in mon keys, however, hair pulling in humans is commonly self-directed [Galski, 1983] and only rarely partner-directed [Buxbaum, 1960], probably because of its socially dis ruptive effect. Since hair is not digestible, hair pulling and eating is unlikely to be adaptive in any evolutionary sense; it may therefore be regarded as a behavioral disor der [see also : Muller and Winkelmann, 1972;Sanchez, 1979;Hassong et al, 1980;Walsh et al, 1982;Fraser and Fox, 1983;Rein hardt, 1984]. The ethopathological aspect of hair pulling was particularly evident in the young female monkey in rank position No.…”
Section: Discussionmentioning
confidence: 99%
“…Partnerdirected hair pulling and eating has also been described in sheep [Fraser and Fox, 1983] and muskox [Reinhardt and Flood, 1983] that are subjected to chronic confinement; feather-picking is probably an analogous be havior occurring in crowded poultry [Fraser and Fox, 1983]. Only two references could be found on hair pulling in monkeys: (1) Elton [1979] mentioned that young females of a baboon group pulled and ate hair of other animals in an artificial-crowding situa tion; (2) Walsh et al [1982] listed self-and partner-directed hair pulling as one of the abnormal behaviors occurring in restrictively reared chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate living conditions-broadly defined-lead to an inability to copulate, incompetent maternal behavior, inappropriate emotional reactions-mainly fear and aggression-to companions, lack of species-typical communicatory signals, and generalized learned helplessness (Brent, 2001;Seligman, 1991;Rogers and Davenport, 1969;Brent et al, 1997). Walsh et al (1982) have listed over 20 behavioral patterns in captive chimpanzees deemed (statistically) abnormal for their unusual frequency, severity or gross anomaly. The list includes bizarre postures, hand clapping, coprophagy, eye poking, spreading of feces, patting of own genitals, hair pulling, head banging, head shaking, head wiping, flipping of the lower lip, ''raspberry'' vocalization (lip pursing and spitting air), rocking, self-clasping, self-mutilation, self-slapping, sticking out the tongue, sucking of objects, such as own body, skin, tongue or penis, urine drinking, wetting of the head with water, and regurgitation and reingestion of food (e.g., Baker, 1996;Gould and Bres, 1986;Morgan et al, 1993).…”
Section: Description Of Psychopathology In Non-human Great Apesmentioning
confidence: 99%